Microbial Interconversion of Alkanes to Electricity - Scheller, Silvan (Frontiers in Energy Research, 2018)
Electricity from fuels can be produced via 2 fundamentally different methods: By burning them to spin generators, or by direct abstraction of electrons at catalysts. The future is the flame-free production of electricity via catalysis, whereby the maximal theoretical yield scales inversely proportional to the process temperature. Low temperature fuel cells are thus needed, but they are not available for hydrocarbons due to the recalcitrant C-H bonds present in alkanes. Fuel cells for alkanes typically require process temperatures higher than 600°C. The microbial pathway of anaerobic alkane oxidation, on the other side, converts alkanes reversibly to single electrons and CO2 at temperatures as low as 4°C. In this perspective, I suggest to utilize this microbial metabolism for catalytic alkane oxidation at low temperatures, in order to convert alkanes to electricity with possibly higher thermodynamic efficiencies as current technologies. Alkane oxidation is partitioned into a biocatalytic (microbial) step to cleave the C-H bonds, and into an electrochemical step for harvest of electricity. In the biocatalytic step, the alkane is oxidized to CO2 and the resulting electrons are loaded onto an electron carrier. Electricity is then generated from the electron-carrier via fuel cells. Due to the intrinsic reversibility of the biochemical pathway, the whole process may be reversed to convert excess electricity (e.g., from solar or wind) with CO2 to alkanes, which is particularly interesting for the alkanes ethane, propane or butane that are easily liquefiable and storable.